Persepsi dan Perilaku Mubaligh terhadap Bank Syariah di Kota Padang - Ardianis, Ardianis (Jurnal AL-AHKAM, 2019)
The variety of product which Syari ‘ah Banking offer gives the citizen an opportunity to choose a bank that suit their needs. How the decision is taken was influenced by perception and attitude, same thing goes for mubaligh. For the growth of bank syari ‘ah it requires a mechanism which could introduce, socialize, and promote bank syari ‘ah into the society.  Socialization can be done by mubaligh. In their religious proselytizing mubaligh could inform about  bank syari ‘ah. The focus  of these research are perception  and attitude mubaligh ‘s  towards  bank syari ‘ah. The pwpose  of this research is to find kinds of factor which influenced mubaligh ‘s perception and attitude in using bank syari ‘ah in padang city.   The sample of this research are mubaligh who lived in padang ‘city and come from influential Islamic organization which are Nahdlatul Ulama, Muhammadiyah, and the Association of Islamic Tarbiyah. The choosing of sample is done with the method pwposive  sampling.  This research is using quantitative approach, while the method which was used in this research is descriptive method. Research shows that the most influencing factor for mubaligh ‘s perception in padang city are personal factor, which are item syari ‘ah banking based on moral/trust in each other and justice, syar‘ah banking applied nisbah, choosing syari’ah banking based on MUI’s fatwa about forbidding contribution. While the most influencing factors for mubal- igh ‘s attitude in padang city is cultural factor, which is item a statement about choosing syari ‘ah banking because syari ‘ah banking are open for global.